2007
DOI: 10.4171/rmi/503
|View full text |Cite
|
Sign up to set email alerts
|

On the regularity of averages over spheres for kinetic transport equations in hyperbolic Sobolev spaces

Abstract: Abstract. We study the smoothing effect of averaging over spheres for solutions of kinetic transport equations in hyperbolic Sobolev spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…We shall see later that there is a natural way to unify the smoothing estimates we seek for these velocity domains, so for the sake of simplicity of the exposition, we focus this introductory discussion on the unit sphere. As proved in the work of In very recent work [1], the purely L 2 -based results in [8] and [7] were significantly extended to estimates of the form…”
Section: Introductionmentioning
confidence: 79%
“…We shall see later that there is a natural way to unify the smoothing estimates we seek for these velocity domains, so for the sake of simplicity of the exposition, we focus this introductory discussion on the unit sphere. As proved in the work of In very recent work [1], the purely L 2 -based results in [8] and [7] were significantly extended to estimates of the form…”
Section: Introductionmentioning
confidence: 79%
“…These averages were studied in [6][7][8]. When the right hand side doesn't contain velocity derivatives it was shown that…”
Section: N Bournaveas and H Wang Nodeamentioning
confidence: 99%
“…We refer the reader to [6][7][8] for a detailed study. In this paper we study velocity averages of the form…”
Section: N Bournaveas and H Wang Nodeamentioning
confidence: 99%
See 2 more Smart Citations